A preliminary account of the Arctic/Subarctic Suberites (Porifera: Demospongiae) fauna - Morozov, Grigori; Strelkova, Natalya Anisimova; Zimina, Olga; Sabirov, Rushan (Zootaxa, 2023)
Sponges of the genus Suberites are quite polymorphic and diverse, yet the delimitation of species within the group has always been challenging since there are only a few spicule types that show little, or sometimes no variation in closely allied species. Koltun (1966) created a variety, S. domuncula var. ficus—something of a “dustbin assemblage”—with a geographic distribution ranging from the North Atlantic, across the Arctic, to the North Pacific Oceans. Our study shows that in the Arctic/Subarctic region, boreal S. ficus is replaced by a mix of closely related species: in the western-Arctic—S. lutkenii, in the eastern-Arctic—S. cebriones. A defining feature—centrotylote microxeas—sets the northern species group apart from the boreal S. ficus and all other congeners known outside the Arctic/Subarctic seas. Altogether, we report seven species and one variety belonging to Suberites from the European Arctic/Subarctic. Five species are Arctic endemics: S. lutkenii, S. spermatozoon, S. montiniger, S. glasenappii, and S. cebriones. One species, S. virgultosus, is a typical boreal. S. syringella is apparently a species complex.